Exploring the influence of electronic word-of-mouth on college students’ purchase intention: an empirical study on the Chinese film industry - Zeng, Meiling (2019)
In the age of the internet, consumers exchange information about products or services through diverse network channels. With its high interactivity, convenience and anonymity, electronic word of mouth has quickly become an emerging hot spot in the marketing field. As the core part of the cultural industry, China’s film industry is in a period of strategic transformation. Electronic word-of-mouth plays a more and more important role in the film industry. To use electronic word of mouth reasonably and effectively in the field of film marketing, it is important to study the influence of various factors of film eWOM on consumer decision-making. College students, with the highest Internet penetration rate and contribution to the Chinese film box office, are selected as the research object of this study. Thus, this dissertation aims to study the influence of electronic word of mouth on college students' film purchase intentions, and provide some implications to China’s film industry and the research field of film consumption behaviours. To achieve these aims, quantitative research methods are selected. After reviewing relevant literature, this dissertation constructs a hypothesis model and proposes 7 research hypotheses. This paper divides the factors influencing eWOM information communication into three categories: the information itself, information source and the receiver. five factors including quantity of eWOM, valence of eWOM and quality of eWOM under information itself; source credibility under information source; internet involvement under the receiver are selected as antecedent variables of the hypothesis model to explore their influence on college students' film purchase intentions. Also, perceived usefulness and perceived credibility are chosen as the mediating variables of this research model to examine their mediating effect between the five factors of eWOM and college students’ purchase intentions. Through empirical research, this paper draws the following four main conclusions :(1) quality of eWOM, quantity of eWOM, source credibility, and internet involvement have a significant impact on perceived usefulness;(2) quantity of eWOM, valence of eWOM and source credibility have a significant impact on both perceived credibility and college students' film purchase intention;(3) perceived usefulness and perceived credibility play an intermediary role in the partial paths of the influence of eWOM on college students' film purchase intentions. Finally, several implications are proposed based on these findings.